Review of Dominik Hangleiter, Jacques Carolan, and Karim P. Y. Thébault's Analogue Quantum Simulation: A New Instrument for Scientific Understanding. - Field, Grace (Philosophy of Science, 2025)
"Analogue Quantum Simulation: A New Instrument for Scientific Understanding" by Dominik Hangleiter, Jacques Carolan, and Karim P. Y. Thébault explores the relationship between analogue quantum simulations and understanding. The book distinguishes between analogue quantum computations and emulations, highlighting their roles in providing different forms of understanding about target systems. Through case studies and theoretical analysis, the authors demonstrate the value of analogue simulations in exploring a wide range of scenarios and phenomena, emphasizing the importance of understanding over mere confirmation in scientific research. The book's insights contribute to advancing the field of analogue simulation and offer valuable perspectives on the diverse roles these simulations can play in scientific inquiry.